Value chain analysis and actors mapping: Case of Tunisia - Dhehibi, Boubaker; Dhraief, Mohamed Zied; Oueslati-Zlaoui, Meriem; Souissi, Asma; Majri, Rihab; Frija, Aymen; Ouerghemmi, Hassen; Alary, Veronique; Ouji, Mourad; Idoudi, Zied; Rudiger, Udo; Rekik, Mourad (International Center for Agricultural Research in the Dry Areas, 2022)
The objective of this report is to analyze, mapping and select the main value chains with potential to integrate the agroecological principles in Tunisia. Based on the secondary data, rapid value chain analysis, focus group discussions at the living labs and participatory approach with the main stakeholders, three value chains were identified in Siliana and Kef governorates: olive oil, sheep meat and honey. The VC assessment according to agroecological principles conducted with the main actors places the olive oil VC as the major value chain with agroecological character. In this sense, an olive oil business model was proposed to encourage the olive producers of SMSA to produce a labeled olive oil to improve their revenues, enhance livelihoods and create a system of values that includes land (terroir).